2022
DOI: 10.1542/peds.2021-052501
|View full text |Cite
|
Sign up to set email alerts
|

Delays Related to Prior Authorization in Inflammatory Bowel Disease

Abstract: BACKGROUND Delays in advancing to biologic therapies are associated with adverse outcomes in inflammatory bowel disease (IBD). Insurer-mandated prior authorizations have been linked to prolonged medication initiation times. We hypothesized that prior authorizations are associated with prolonged biologic initiation time and increased IBD-related healthcare utilization among children with IBD. METHODS We performed a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Another recent study found that prior authorization and complicated authorizations requiring appeal, step therapy, or P2P were associated with 10.2- and 24.6-day increases in biologic initiation time, respectively. 11 In that same study, prior authorizations were associated with a 12.9% increased likelihood of IBD-related healthcare utilization within 180 days of biologic recommendation and a 14.1% increased likelihood of corticosteroid dependence at 90 days.…”
Section: Discussionmentioning
confidence: 87%
“…Another recent study found that prior authorization and complicated authorizations requiring appeal, step therapy, or P2P were associated with 10.2- and 24.6-day increases in biologic initiation time, respectively. 11 In that same study, prior authorizations were associated with a 12.9% increased likelihood of IBD-related healthcare utilization within 180 days of biologic recommendation and a 14.1% increased likelihood of corticosteroid dependence at 90 days.…”
Section: Discussionmentioning
confidence: 87%
“…They also showed that complicated PA was associated with 24.6-day increase in biologic initiation time (13). Additionally, PA was associated with 12.9% increase likelihood of IBD-related health care utilization and 14.1% increased likelihood of corticosteroid dependence at 90 days, an important outcome measure in IBD (13). Patients with EoE have a high annual health care cost when compared to the general population, estimated at $1.4 billion in the United States (14).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease signifies disorders involving chronic inflammation of the digestive tract, that is, a type of inflammatory disease that affects the rectum and colon. 1 The treatment mainly includes drug therapy and surgery. More effective drugs are to be developed to improve treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a noninfectious, chronic, and recurrent inflammation of the gastrointestinal tract. 1,2 Common symptoms of IBD include diarrhea, rectal bleeding, abdominal pain, fatigue, and weight loss. 3,4 It is important to diagnose IBD.…”
Section: Introductionmentioning
confidence: 99%